Children's vocabulary and friendships: A comparative study between children with and without Specific Learning Disorder and Attention Deficit Hyperactivity Disorder. (9th February 2022) - Kouvava, Sofia; Antonopoulou, Katerina; Ralli, Asimina M.; Kokkinos, Constantinos M.; Maridaki‐Kassotaki, Katerina
Abstract : Language skills are important in the formation and maintenance of friendships. Children with specific learning disorder (SLD) or attention‐deficit/hyperactivity disorder (ADHD) experience difficulties with their relationships and have language‐related problems. This study aims to examine how expressive and receptive vocabulary may relate to friendships of children with and without SLD or ADHD. Participants were 64 children with SLD, 64 children with ADHD, and 64 typically developing (TD) children, aged 8–12 years (Mage = 9.77 years, SD = 1.22), attending Grades 3 to 6 in inclusive primary schools of Attica, Greece. The Greek versions of the Peabody Picture Vocabulary Test and the expressive vocabulary subscale of the WISC‐III were administered along with the sociometric nominations of friends and the self‐reports of best friendship duration. Results showed that children with SLD and ADHD reported best friendships of shorter duration and had significantly poorer receptive and expressive vocabulary. Children with ADHD had significantly fewer close and best friends than children with SLD, who in turn had significantly fewer close and best friends than the TD children. Children's vocabulary in all three groups was positively correlated with the duration of their best friendships and was found to moderately predict children's close friendships.